Intertemporal Resource Economics An Introduction to the Overlapping Generations Approach - Farmer, Karl.; Bednar-Friedl, Birgit; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This monograph provides a concise introduction to the overlapping generations approach to the intertemporal economics of renewable natural resources. In contrast to the dominant infinitely-lived agent (ILA) approach it acknowledges that natural resources typically outlive the individuals who use them. Finite lifetimes, generations overlap and competing natural and man-made capital facilitate long-run intergenerational inefficiency and inequity (unsustainability) of market allocations. While avoiding any presumption of either doomsday or a golden age, the book investigates the structural and institutional preconditions needed to ensure that renewable resources are used efficiently and equitably across generations. The primary aim of this book is to provide an easy-to-follow guide to the analytically much more demanding journal literature. This is achieved by using the same model type throughout the book and by adhering to functional specifications that allow for explicit equilibrium solutions.
Basics -- Economic Growth and Natural Resources -- Efficiency and Market Equilibrium under Resource Abundance -- Intergenerational Efficiency in Log-linear Cobb-Douglas OLG Models -- Intertemporal Market Equilibrium and Short-Run Intergenerational Efficiency -- Steady-State Market Equilibrium, Long-Run Intergenerational Efficiency, and Optimality -- Efficiency and Market Equilibrium with Scarce Renewable Resources -- Renewable Resources and Intergenerational Efficiency -- Intertemporal Market Equilibrium and Intergenerational Efficiency with Renewable Resources -- Intergenerational Equity and Market Equilibrium with Scarce Renewable Resources -- Sustainable Economic Growth with Linear Resource Regeneration -- Steady-State Sustainability under Logistically Regenerating Resources -- Shocks to Harvest Technology and Natural Regeneration -- Resource Use with Physical Harvest Costs -- Effects of Harvest Cost and Biological Shocks.
Keywords: Economics; Environmental economics; Economics/Management Science; Environmental Economics